Computer-supported collaborative learning with digital video cases in teacher education: the impact of teaching experience on knowledge convergence - Zottmann, Jan M.; Stegmann, Karsten; Strijbos, Jan-Willem; Vogel, Freydis; Wecker, Christof; Fischer, Frank (Elsevier, 2013)
Case-based learning is ascribed high potential with respect to the education of pre-service teachers as well as the further education of experienced in-service teachers, as it can provide opportunities for the application of professional knowledge to authentic classroom situations. In addition to the application and acquisition of knowledge, the aspect of knowledge convergence (i.e., increasing similarity of collaborative learners with respect to their knowledge) should be taken into account when homogeneous benefits are desired for all participants of a case-based training. A field study with 29 pre-service teachers and 24 in-service teachers from adult education was conducted to examine effects of different levels of teaching experience on knowledge application, knowledge acquisition, and knowledge convergence in a computer-supported collaborative case-based learning environment. An innovative approach to measuring knowledge convergence was introduced, using the positions of annotations (i.e., flags placed on the timeline of the case video) made by learners during their case analyses as an indicator of their shared focus of attention. This measure was found to positively correlate with the application and acquisition of professional knowledge. Teaching experience affected both processes and outcomes of case-based learning, suggesting different means of instructional support for pre-service and in-service teachers.